2019
DOI: 10.1002/iub.2187
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the LncRNA Gpr19 attenuates ischemia‐reperfusion injury after acute myocardial infarction by inhibiting apoptosis and oxidative stress via the miR‐324‐5p/Mtfr1 axis

Abstract: Reperfusion therapy after acute myocardial infarction (AMI) can effectively restore the blood supply and nutritional support of ischemic myocardium and save the dying myocardium. However, myocardial ischaemia‐reperfusion (I/R) injury has become a new threat to reperfusion therapy for AMI. Many long‐chain noncoding RNAs (lncRNAs) are dysregulated by I/R damage. Of these dysregulated lncRNAs, Gpr19 was selected as a potential gene of interest based on its high expression change. We aimed to explore the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“… 28 Several studies have reported that lncGpr19, lncH19, and lncTPT1-AS1 can absorb miR-324-5p, thereby influencing the migration of cancer cells. 29 , 30 , 31 In this study, we found that miR-324-5p targets lncDum and inhibits the differentiation of C2C12 myoblasts. lncDum can promote the differentiation of skeletal muscle satellite cells by inhibiting the expression of Dppa2 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 28 Several studies have reported that lncGpr19, lncH19, and lncTPT1-AS1 can absorb miR-324-5p, thereby influencing the migration of cancer cells. 29 , 30 , 31 In this study, we found that miR-324-5p targets lncDum and inhibits the differentiation of C2C12 myoblasts. lncDum can promote the differentiation of skeletal muscle satellite cells by inhibiting the expression of Dppa2 .…”
Section: Discussionmentioning
confidence: 60%
“…N -acyl amino acid is an endogenous uncoupler of mitochondrial respiration that promotes mitochondrial oxidative metabolism without the production of ATP. 39 miR-324-5p has also been reported to promote apoptosis and oxidative stress by targeting Mtfr1 , 29 indicating that miR-324-5p is tightly associated with mitochondrial function. As lipid deposition requires mitochondrial-provided ATP, 40 we hypothesize that miR-324-5p promotes oleate-induced lipid deposition in C2C12 myoblasts by improving mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism involves inactivation of the NF‐ κB signal pathway induced by the lack of Mirt1 41 . Meanwhile, inhibition of lncRNA Gpr19 and overexpression of lncRNA UVA1 are proved to attenuate cardiac injury after MI by inhibiting apoptosis via the miR‐324‐5p/Mtfr1 axis and miR‐143/MDM2/p53 axis, respectively 42,43 …”
Section: Lncrnas and Cardiovascular Diseasesmentioning
confidence: 99%
“…For example, knockout of lncRNA Mirt1, which is mainly expressed in cardiac fibroblasts, reduces apoptosis in cardiomyocytes and infiltration of inflammatory cells into the heart thereby improving cardiac function.The underlying mechanism involves inactivation of the NF-κB signal pathway induced by the lack of Mirt1 41. Meanwhile, inhibition of lncRNA Gpr19 and overexpression of lncRNA UVA1 are proved to attenuate cardiac injury after MI by inhibiting apoptosis via the miR-324-5p/Mtfr1 axis and miR-143/MDM2/p53 axis, respectively 42,43.…”
mentioning
confidence: 99%
“…Acute myocardial infarction (AMI) has becoming a common and potential life-threatening disease with an increasing incidence and high mortality due to the acute interruption of myocardial blood ow which then lead to ischemic myocardial necrosis [1,2]. Reperfusion therapy after AMI can effectively restore the blood supply and nutritional support in ischemic myocardium and even save the dying myocardium [3]. The pathogenesis of AMI was identi ed to be associated with multiple reasons and cardiomyocyte apoptosis was considered as the crucial components [4,5].…”
Section: Introductionmentioning
confidence: 99%